2020
DOI: 10.4103/joacp.joacp_100_19
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided transversus abdominis plane block versus caudal block for postoperative analgesia in children undergoing inguinal hernia surgery: A comparative study

Abstract: Background and Aims: Ultrasound-guided (USG) transversus abdominis plane (TAP) block has emerged as a safe and effective regional anesthesia technique as it provides adequate postoperative pain relief for lower abdominal surgeries. Caudal block is a gold standard technique in pediatric surgeries. Our aim was to compare the duration of postoperative analgesia between TAP block and caudal block in children undergoing inguinal hernia surgeries. Material and Methods: In a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 12 publications
(10 reference statements)
0
20
0
Order By: Relevance
“…Finally, 69 eligible RCTs were included for qualitative and quantitative analyses. 22–90 A PRISMA flow diagram of the evidence selection process is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 69 eligible RCTs were included for qualitative and quantitative analyses. 22–90 A PRISMA flow diagram of the evidence selection process is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The TAP block, which was previously performed using a blind technique but then became more reliable with the introduction of the US, it has become one of the most preferred methods for pain management, especially after pediatric abdominal surgery. A previous study which compares US-guided TAP block and caudal block for postoperative analgesia in children undergoing inguinal hernia surgery shows that the TAP block provided prolonged analgesia and a lower total amount of rescue analgesic consumption 6-24 hours after the block placement compared to caudal block 15 . Priyanka P Karnik et al observed that the pain scores in the TAP block group were considerably lower in the first 2 hours compared to the local infiltration group 16 .…”
Section: Discussionmentioning
confidence: 99%
“…USG-guided TAP block was compared with CE block after lower abdominal surgery for postoperative analgesia in one study and was found more effective [8]. In another study, the USG-guided TAP block provided superior analgesia with less demand for rescue analgesia dose than the CE block in children after inguinal herniotomy [6]. As well, in the pediatric patient population, the postoperative analgesic benefits of USG-guided DPNB and CE block were compared after distal hypospadias surgery and circumcision, and in both studies, USG-guided DPNB provided superior analgesia than CE block [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…With USG guidance, transversus abodominis plane (TAP) block has become a widely used method for surgical anesthesia and postoperative analgesia under anesthesia or sedation, similar to CEA [3,5]. With TAP block, nerves belonging to the T7-L1 spinal afferents responsible for inguinal dermatomal innervation of the body can be blocked in the space between the transversus abdominis and the internal oblique muscles [6]. In providing postoperative pain control, transversus abdominis plane block can produce either equivalent or superior postoperative analgesia to caudal block [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation